O uso de plantas medicinais como estratégia motivacional para aprendizagem sobre Botânica - Abreu, Edir de (2019)
Motivation for learning on any subject has been a great challenge for teachers, who unable to achieve positive results in their classes, especially regarding the development of skills and competences. When it comes to the often complex botany content, traditional teaching methods generate little involvement and little learning for students. This work proposes to use the knowledge of their own students about medicinal plants as a motivating element for learning botanical contents in High School, using an investigative methodology. Considering that the Guidelines of the National Policy of Medicinal and Phytotherapeutic Plants (PNPMF), of Ministry of Health, propose the inclusion on the theme in all levels of school education, providing a meaningful learning opportunity. In the Mato Grosso State, the consumption of these plants is part of the daily life of several citizens. Thus, this work aimed to contribute to the motivation of learning Botany, facilitating the development of argumentation, and skills such as: questioning, experimentation and synthesis from the prior knowledge of students about the use of medicinal plants. This work is guided by the principles of active teaching methods, encouraging students to think about investigative activities with medicinal plants, providing the meaningful learning process through activities such as paper chromatography, botanical structure analysis, water capture from the process of plant transpiration and cytotoxicity test of medicinal plants. It was concluded that most students make use of plants for medicinal purposes and that guidance on the use of this refusal is necessary. Working actively and investigatively with medicinal plants facilitates the development of skills and competences and enables botanical knowledge of both morphological structures and physiological processes. Ethnology about medicinal plants is a potential element to increase students’ intrinsic and extrinsic motivation. The study also reveals the need for all actors in the school community to deepen their knowledge of medicinal plants in order to begin to understand and extract subsumers of the implementation of meaningful learning of botanical concepts and contents.